2010
DOI: 10.1158/1078-0432.ccr-09-2456
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and In vivo Selective Antitumor Activity of Edelfosine against Mantle Cell Lymphoma and Chronic Lymphocytic Leukemia Involving Lipid Rafts

Abstract: Purpose: Mantle cell lymphoma (MCL) and chronic lymphocytic leukemia (CLL) remain B-cell malignancies with limited therapeutic options. The present study investigates the in vitro and in vivo effect of the phospholipid ether edelfosine (1-O-octadecyl-2-O-methyl-rac-glycero-3-phosphocholine) in MCL and CLL.Experimental Design: Several cell lines, patient-derived tumor cells, and xenografts in severe combined immunodeficient mice were used to examine the anti-MCL and anti-CLL activity of edelfosine. Furthermore,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
96
0
18

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(127 citation statements)
references
References 36 publications
13
96
0
18
Order By: Relevance
“…3A). Alkyl-lysophospholipid analogs (e.g., edelfosine and, to a lesser extent, perifosine) incorporate into lipid rafts, modify their organization, and can selectively induce programmed cell death in CLL and lymphoma cells (17,18). We found that edelfosine (and, to a much lesser extent, perifosine) significantly reduced aggregation upon prolonged incubation with CLL cells (Fig.…”
Section: Characterization Of the Cd19-responsive Subpopulation Of Cllmentioning
confidence: 67%
See 1 more Smart Citation
“…3A). Alkyl-lysophospholipid analogs (e.g., edelfosine and, to a lesser extent, perifosine) incorporate into lipid rafts, modify their organization, and can selectively induce programmed cell death in CLL and lymphoma cells (17,18). We found that edelfosine (and, to a much lesser extent, perifosine) significantly reduced aggregation upon prolonged incubation with CLL cells (Fig.…”
Section: Characterization Of the Cd19-responsive Subpopulation Of Cllmentioning
confidence: 67%
“…CLL cells (1 3 10 6 ) were separately mixed in the presence or in the absence of the following: 25 or 50 mg/ml anti-human CD21 (clone Bu32), 2.5 mg/ml anti-human CD62L (clone DREG-56), and 40 mg/ml anti-human b 2 integrin (clone P4H9-A11), all for 30 min; 10 mM MbCD for 5, 10, and 30 min; 20 mM cytochalasin B for 30 min; 10, 20, or 50 mM Syk inhibitor II, 70 mM genistein, 3 mM herbimycin A, or 1, 5, or 10 mM edelfosine or perifosine for 1 or 24 h; and 1, 5, 10, or 20 mM PP2 for 15 min or 2 h. These concentrations were established according to previous publications (17)(18)(19)(20)(21)(22)(23) and were titrated in this study to obtain a maximal effect without killing the cells. Controls used included Abs as isotype controls.…”
Section: Inhibitorsmentioning
confidence: 99%
“…Edelfosine (ET) (1-O-octadecyl-2-O-methyl-snglycero-3-phosphocholine) is the prototype of a promising class of anticancer drugs known as synthetic alkyl-lysophospholipids (ALPs), which selectively target tumor cells sparing healthy ones [5]. ET is active against several tumor cell lines [5][6][7]. The exact mechanism of action of ET still remains to be fully elucidated, but it has been proved that it accumulates in membrane lipid rafts by recruiting and promoting clustering of Fas/CD95 receptors [6,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…activity (10). Although different types of alkylphospholipids depend on the same modes of cellular uptake, it appears that observed differences in kinetics and efficiencies may depend on variations in the importance of singular pathways, e.g., raft-mediated endocytosis via ATP-dependent translocase activity (15,16).…”
Section: A B C Dmentioning
confidence: 99%
“…Various studies have shown that perifosine accumulates in lipid rafts in a manner sensitive to raft disruption by cholesterol depletion (9)(10)(11). Subsequently, it was suggested that LFG, an anti-apoptotic protein with subcellular localization in lipid rafts, may interfere with perifosine-induced apoptosis.…”
Section: Introductionmentioning
confidence: 99%